Ethyl esters production catalyzed by immobilized lipases is influenced by n-hexane and ter-amyl alcohol as organic solvents - Pires Borges, Janaina; Quilles Junior, José Carlos; Moreno-Pérez, Sonia; Fernández-Lorente, Gloria; Boscolo, Mauricio; Gomes, Eleni; Silva, Roberto da; Alonso Bocchini, Daniela; Guisán, José Manuel (Bioprocess and Biosystems Engineering, 2020)
Lipase stability in organic solvent is crucial for its application in many biotechnological processes as biocatalyst. One way to improve lipase’s activity and stability in unusual reaction medium is its immobilization on inert supports. Here, lipases from different sources and immobilized through weak chemical interactions on hydrophobic and ionic supports had their transesterification ability dramatically dependent on the support and also on the solvent that had been used. The ethanolysis of sardine oil was carried out at the presence of cyclohexane and tert-amyl alcohol, in which Duolite A568-Thermomyces lanuginosa lipase derivative achieved 49% of ethyl esters production after 24 h in cyclohexane. The selectivity of immobilized lipases was also studied and, after 3 h of synthesis, the reaction with Duolite A568-Thermomyces lanuginosa derivative in cyclohexane produced 24% ethyl ester of eicosapentaenoic acid and 1.2% ethyl ester of docosahexaenoic acid, displaying a selectivity index of 20 times the ethyl ester of eicosapentaenoic acid. Different derivatives of Candida antarctica lipases fraction B (CALB) and phospholipase Lecitase® Ultra (Lecitase) were also investigated. Along these lines, a combination between these factors may be applied to improve the activity and selectivity of immobilized lipases, decreasing the total cost of the process. The authors thank the financial support from the São Paulo Research Foundation (FAPESP – grants 2012/09054-3 and 2013/00530-0), and the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior—Brasil (CAPES – grant number 3894/13-4). Peer reviewed